Does Unemployment Hurt Less if There Is More of It Around? A Panel Analysis of Life Satisfaction in Germany and Switzerland - Daniel Oesch; Oliver Lipps (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
This paper examines the existence of a habituation effect to unemployment: Do the unemployed suffer less from job loss if unemployment is more widespread, if their own unemployment lasts longer and if unemployment is a recurrent experience? The underlying idea is that unemployment hysteresis may operate through a sociological channel: if many people in the community lose their job and remain unemployed over an extended period, the psychological cost of beingunemployed diminishes and the pressure to accept a new job declines. We analyze this question with individual-level data from the German Socio-Economic Panel (1984-2009) and the Swiss Household Panel (2000-2009). We find no evidence for a mitigating effect of high surrounding unemployment on unemployed individuals' subjective well-being: Becoming unemployed hurts as much when regional unemployment is high as when it is low. Likewise, the strongly harmful impact of being unemployed on well-being does not wear off over time, nor do repeated episodes of unemployment make it any better. It thus appears doubtful that an unemployment shock becomes persistent because the unemployed become used to, and hence reasonably content with, being without a job.
Keywords: 330; Subjective well-being; unemployment; hysteresis; happiness; social norm; Arbeitslosigkeit; Hysterese; Sozialpsychologie; Zufriedenheit; Lebensqualität; Deutschland; Schweiz